Feasibility Study of Integrated Rest Area Project of Taman Mini Indonesia Indah - Hendra Gunawan; Eka Pria Anas (Syntax Literate, 2022)
The Integrated Rest Area Project of Taman Mini Indonesia Indah is one of transit oriented development in a strategic location because it’s the starting point for commuters from around the east and south of Jakarta (Pondok Gede, Bekasi, Cibubur, and surrounding areas). Another strategic aspect is the existence of Inner City toal roads, Jagorawi toll roads, JORR toll roads, Halim Perdanakusuma Airport, LRT, Tamini Square Shopping Center, and Taman Mini Indonesia Indah, which are aimed for the upper and middle class with the target of young professionals and public. This research aims to determine the feasibility of the Integrated Rest Area Project of Taman Mini Indonesia Indah when viewed from the aspects of feasibility study by making an analysis of the sensitivity of the Integrated Rest Area of Taman Mini Indonesia Indah to the impact of variable changes on NPV with optimistic, most likely, and pessimistic scenarios, and analyze the impact of changes in capital structure on project financing that affect the project's NPV. Based on the assumptions, the integrated Rest Area Project of Taman Mini Indonesia Indah is feasible to do because it produces a positive Net Present Value, IRR > discount factor, PI > 1 and Payback Period before the operating period. The use of 40% of loans turns out to produce the most optimal NPV. This project is feasible.